In search of El Dorado: U.S. experts and the promise of development in the Guayana region of Venezuela. (3rd July 2019) - Schulze, Frederik
ABSTRACT: When urban planners from MIT and Harvard University began to design a new city in Venezuela in 1961, euphoria soon gave way to a skeptical appraisal of urban planning. Unrealistic ambitions, inadequate implementation, social tensions, and diverging interests by US American und Venezuelan experts complicated the building of Ciudad Guayana. The evolving city did not live up to initial expectations and remained a work in progress. Tracing the many voices involved including critics within the American team, helps understand the dynamics, challenges, and limitations of knowledge transfers in 1960s modernization programs. Scientific planning knowledge proved an unstable and less powerful commodity than Americans had expected. Problems on the ground took the gloss off the Western hegemonic scientific repertoire. They led to an appropriation of knowledge by Venezuelan experts who harnessed their US American counterparts to advance their own political aims.